Wednesday

August 20, 2014

August 20, 2014

Posted by **tatiana** on Monday, October 3, 2011 at 8:26pm.

- pre-calculus -
**Reiny**, Monday, October 3, 2011 at 9:04pmI am sure you meant to say

sinx/(sinx+cosx) = tanx/(1+tanx)

RS = (sinx/cosx)/[1 + sinx/cosx]

= (sinx/cosx)/[(cosx+sinx)/cosx]

= (sinx/cosx) ( cosx/(cosx + sinx))

= sinx/(cosx + sinx)

= LS

**Related Questions**

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

maths - trigonometry - I've asked about this same question before, and someone ...

Math - Im really struggling with these proving identities problems can somebody ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Pre-calc - prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i ...

Pre-Calculus - How do you verify: 1.) sinxcosx+sinx^3secx=tanx 2.) (secx+tanx)/(...

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...